Late diagnosis of chronic granulomatous disease. (13th July 2020) - Barkai, T; Somech, R; Broides, A; Gavrieli, R; Wolach, B; Marcus, N; Hagin, D; Stauber, T
Summary: Modern era advancements in medical care, with improved treatment of infections, can result in delayed diagnosis of congenital immunodeficiencies. In this study we present a retrospective cohort of 16 patients diagnosed with Chronic Granulomatous Disease (CGD) at adulthood. Some of the patients had a milder clinical phenotype, but others had a classic phenotype with severe infectious and inflammatory complications reflecting a profoundly impaired neutrophil function. It is therefore of great importance to investigate the individual journey of each patient through different misdiagnoses and the threads which led to the correct diagnosis. Currently the recommended definitive treatment for CGD is hematopoietic stem cell transplantation (HSCT). Although survival of our patients to adulthood might argue against the need for early HSCT during infancy, we claim that the opposite is correct, as most of them grew to be severely ill and diagnosed at a stage when HSCT is debatable with potentially an unfavorable outcome. This cohort stresses the need to increase awareness of this severe congenital immunodeficiency among clinicians of different specialties who might be treating undiagnosed adult patients with CGD. Graphical Abstract: